2021
DOI: 10.3390/cancers13184650
|View full text |Cite
|
Sign up to set email alerts
|

A New Player in Neuroblastoma: YAP and Its Role in the Neuroblastoma Microenvironment

Abstract: Neuroblastoma is the most common extra-cranial pediatric solid tumor that accounts for more than 15% of childhood cancer-related deaths. High risk neuroblastomas that recur during or after intense multimodal therapy have a <5% chance at a second sustained remission or cure. The solid tumor microenvironment (TME) has been increasingly recognized to play a critical role in cancer progression and resistance to therapy, including in neuroblastoma. The Yes-Associated Protein (YAP) in the Hippo pathway can regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 181 publications
(304 reference statements)
0
5
0
Order By: Relevance
“…Several studies showed that VPF-mediated YAP inhibition leads to a decrease in tumor cell proliferation, migration, and survival in vitro and suppression of tumor growth and progression in vivo 27,38,46,51 . With recent evidence of YAP/TAZ role in NB tumorigenicity, metastatic progression, treatment resistance and tumor relapse 13,14,17,18,52 , we aimed to investigate whether VPF can also be used as a potential therapeutic agent against NB.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that VPF-mediated YAP inhibition leads to a decrease in tumor cell proliferation, migration, and survival in vitro and suppression of tumor growth and progression in vivo 27,38,46,51 . With recent evidence of YAP/TAZ role in NB tumorigenicity, metastatic progression, treatment resistance and tumor relapse 13,14,17,18,52 , we aimed to investigate whether VPF can also be used as a potential therapeutic agent against NB.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that VPF-mediated YAP inhibition leads to a decrease in tumor cell proliferation, migration, and survival in vitro and suppression of tumor growth and progression in vivo 27,38,46,51 . With recent evidence of YAP/TAZ role in NB tumorigenicity, metastatic progression, treatment resistance and tumor relapse 13,14,17,18,52 , we aimed to investigate whether VPF can also be used as a potential therapeutic agent against NB.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have described the contribution of the Hippo tumor suppressor pathway downstream effectors YAP (Yes-associated protein) and TAZ (transcriptional co-activator with PDZ-binding motif; WWTR1) in NB tumorigenesis, treatment resistance and relapse, highlighting the functional relevance of targeting YAP/TAZ in NB tumors [13][14][15][16][17][18][19][20][21][22] . YAP/TAZ are transcriptional co-activators that play a central role in stem cell modulation and tissue regeneration [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized that the crosstalk between tumor cells and stromal cells, such as fibroblasts and endothelial cells, contributes to tumor growth and progression. Increased expression/activity of the transcriptional co-regulator Yes-Associated Protein (YAP) following chemotherapy and relapse promotes resistance to therapy, including resistance to anti-disialoganglioside 2 (anti-GD2) immunotherapy, in high-risk neuroblastoma through the transcriptional repression of genes that play a role in the TME [ 41 , 42 ]. However, the role of YAP expression, as well as that of other factors in other solid tumors, has not been thoroughly evaluated.…”
Section: The Tme In Solid Tumorsmentioning
confidence: 99%